Palaeogenetics of western French sturgeons spotlights the relationships between Acipenser sturio and Acipenser oxyrinchus. (16th November 2012) - Chassaing, Olivier; Desse‐Berset, Nathalie; Duffraisse, Marilyne; Hughes, Sandrine; Hänni, Catherine; Berrebi, Patrick; McClain, Craig
Abstract Aim The Atlantic sturgeon, Acipenser oxyrinchus, was long considered an American species, but recent discoveries based on analyses of archaeological remains proved its presence in the Baltic Sea and in France. This came as a surprise, as the European sturgeon, Acipenser sturio, was thought to be the only sturgeon species present on the European Atlantic coast. It was hypothesized that migrants from North America founded the Baltic population of Atlantic sturgeons around 1200 years ago. Location The sampling is composed of five sturgeon archaeological remains (5000–1800 yr bp) and 21 naturalized or ethanol‐preserved museum specimens from the 19th and 20th centuries, originating from the French Atlantic coast. Methods Analyses of ancient DNA were performed following the strict criteria of the field to avoid contamination and to ensure sequence authentication. A 210‐bp fragment of the control region (CR) was sequenced and three microsatellite loci were sized and sequenced. Results Out of a total of 26 samples, three archaeological remains and six museum specimens produced A. oxyrinchus mitochondrial or nuclear sequences; two of these museum samples showed signs of hybridization between A. sturio and A. oxyrinchus. All the other samples yielded only A. sturio DNA sequences, and a new CR haplotype was described in this species. Main conclusions Molecular evidence of sympatry and natural hybridization between A. sturio and A. oxyrinchus on the French Atlantic coast – specifically the hybrid evidence of two museum specimens collected from the Seine River in 1823 and 1858 – challenge our understanding of the species' past relationships. In light of these findings, new hypotheses are presented to explain the history and geographical range of A. oxyrinchus in Europe.